Functional Changes in Neocortical Activity in Huntington's Disease Model Mice: An in vivo Intracellular Study - Stern, Edward A. (Frontiers in Systems Neuroscience, 2011)
Studies of animal models of Huntington's disease (HD) have revealed that neocortical and neostriatal neurons of these animals in vitro exhibit a number of morphological and physiological changes, including increased input resistance and changes in neocortical synaptic inputs. We measured the functional effects of polyglutamate accumulation in neocortical neurons in R6/2 mice (8–14 weeks of age) and their age-matched non-transgenic littermates using in vivo intracellular recordings. All neurons showed spontaneous membrane potential fluctuations. The current/voltage and the firing properties of the HD neocortical neurons were significantly altered, especially in the physiologically relevant current range around and below threshold. As a result, membrane potential transitions from the Down state to Up state were evoked with smaller currents in HD neocortical neurons than in controls. The excitation-to-frequency curves of the HD mice were significantly steeper than those of controls, indicating a smaller input–output dynamic range for these neurons. Increased likelihood of Down to Up state transitions could cause pathological recruitment of corticostriatal assemblies by increasing correlated neuronal activity. We measured coherence of the in vivo intracellular recordings with simultaneously recorded electrocorticograms. We found that the peak of the coherence at <5 Hz was significantly smaller in the HD animals, indicating that the amount of coherence in the state transitions of single neurons is less correlated with global activity than non-transgenic controls. We propose that decreased correlation of neocortical inputs may be a major physiological cause underlying the errors in sensorimotor pattern generation in HD.